Identification of lncRNA DLEU2 as a potential diagnostic biomarker and anti-inflammatory target for ulcerative colitis - Lin, Qiuling; Zhang, Dingguo; Zhang, Jian; Luo, Weixiang; Xu, Zhenglei; Yao, Jun; Wang, Lisheng (Frontiers in Pharmacology, 2022)
The incidence of ulcerative colitis (UC) in China has significantly increased over the past ten years. Here we aim to explore potential diagnostic biomarkers and anti-inflammatory targets associated with UC. Patients with UC were enrolled in this study. The expression of lncRNAs and mRNAs in the nidus of the gut mucosa and adjacent normal mucosa samples was evaluated by RNA sequencing. The role of DLEU2 in inflammation and NF-κB signaling pathway was examined by RT-qPCR, Western blotting, and ELISA with human macrophage-like cells derived from THP-1. 564 lncRNAs and 859 mRNAs are significantly altered in the nidus of the gut mucosa of UC patients. Among the differentially expressed lncRNAs, DLEU2 changes the most. The expression of DLEU2 is negatively associated with inflammatory factors such as TNF-α, IL-1α, IL-1β, IL-6, and NLRP3. Mechanistically, DLEU2 exerts anti-inflammatory activity by inhibiting the NF-κB signaling pathway. In conclusion, the lncRNA DLEU2 in the intestinal mucosa is dysregulated upon gut inflammation and may act as a diagnostic biomarker and a therapeutic target for UC.